Sotetsuflavone inhibits proliferation and induces apoptosis of A549 cells through ROS-mediated mitochondrial-dependent pathway - Shaohui Wang; Yanlan Hu; Yu Yan; Zhekang Cheng; Tongxiang Liu (BMC, 2018)
Abstract Background Sotetsuflavone is isolated from Cycas revoluta Thunb., which has biological activity against tumors. However, the anti-proliferative effects of sotetsuflavone on A549 cells and its mechanism are not fully elucidated. Methods This study investigated the mechanisms of growth inhibition, cell cycle arrest and apoptosis in non-small cell lung cancer A549 cells induced by sotetsuflavone and evaluated whether sotetsuflavone can be safely utilized by humans as therapeutic agent. Results We found that sotetsuflavone had significant antiproliferative activity against A549 cells. At the same time, the reactive oxygen species (ROS) content increased while the mitochondrial membrane potential and the ratio of Bcl-2/Bax decreased. Cleaved caspase-3, cleaved caspase-9, cytochrome C and Bax expression increased, and Cyclin D1, CDK4, cleaved caspase-8 and Bcl-2 expression decreased. Interestingly, we demonstrated that sotetsuflavone could effectively inhibit the G0/G1 cycle progression, and then induce the endogenous apoptosis pathway. Our results show that sotetsuflavone could inhibit the growth of A549 cells by up-regulating intracellular ROS levels and causing the mitochondrial membrane potential to collapse, inducing G0/G1 phase arrest and endogenous apoptosis. Conclusions In short, we confirm that sotetsuflavone had an inhibitory effect on A549 cells and discovered that it causes apoptosis of A549 lung cancer cells. Sotetsuflavone may be used as a novel candidate for anti-tumor therapy in patients with lung cancer.